PENGARUH PRICE, PROMOTION DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN PADA OLSHOP CRAFTY STORE DI WATES - Fitri Ana Dewi Nur Aini; Miftahul Munir; Baju Pramutoko (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to test and explain the influence price, promotion and facilities for purchasing decisions Olshop Crafty Store limit partially and simultaneously. This research uses quantitative methods and the population studied is all consumers who make purchases at Olshop Crafty Store Wates for 1 month of research. The number of samples taken was 93 respondents, and the sampling method was used purposive sampling. Data collected through questionnaires, while analysis techniques use validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t tests, f tests and R determinant tests2. The research results show that (1) price partially has a significant effect on purchasing decisions with a sig value. 0.001 < than 0.05, (2) promotion partially has a significant effect on purchasing decisions with a sig value. 0.000 < 0.05, (3) facilities partially have a significant effect on purchasing decisions with a sig. 0.000 < than 0.05, (4) price, promotion and facilities simultaneously have a significant effect on purchasing decisions with a sig value. F 0.000 < 0.05. Purchase decision in Olshop Crafty Store Wates is influenced by these three variables amounting to 66.2% while the remaining 33.8% is influenced by other factors outside this research.